Impact of Corporate Social Responsibility, Morality and Servant Leadership on Employee Performance - Pervaiz, Uzma (2024)
This study investigates the impact of employee-centric embedded corporate social responsibility (CSR) and servant leadership on the contextual performance of staff nurses in the public sector of Pakistan. It also examines the roles of moral identity as a moderating variable and affective organisational commitment as a mediating variable. Contextual performance, encompassing the non-technical aspects of a nurse's job, is crucial for the overall effectiveness and efficiency of healthcare delivery. The study explores how these factors influence the contextual performance of staff nurses in Pakistan's public health hospitals. The philosophy of this study was positivism due to its quantitative nature. The researcher identified variables and developed eight hypotheses using Social Exchange Theory (SET). A research strategy was designed to collect data on observed reality, employing purposive sampling to gather data from 350 staff nurses in public sector hospitals in Rawalpindi/Islamabad, Pakistan. The questionnaire used for data collection was adapted from previous related research. A pilot study was conducted to assess the reliability and validity of the questionnaire. Cronbach's Alpha was used to evaluate these metrics, and the results showed that all values were above the acceptable threshold 0.7. Partial Least Squares Structural Equation Modeling (PLS-SEM) using Smart-PLS software was employed to test and confirm the causal relationships between the proposed hypotheses, with the goal of creating law-like generalizations for future testing. The structural model in PLS-SEM evaluated theoretical relationships and hypotheses concerning both direct and indirect effects among variables and estimated parameters for these relationships (paths). It also analysed complex relationships, including mediation and moderation, and assessed the overall model fit. The findings reveal a significant positive relationship between employee centric embedded CSR and contextual performance of nurses, as well as between servant leadership and nurses' contextual performance. Furthermore, affective organisational commitment was found to partially mediates the relationship between both employee-centric embedded CSR and contextual performance, and servant leadership and contextual performance. However, the study did not find a significant moderating effect of moral identity on the relationship between employee-centric embedded CSR and affective organisational commitment. This suggests that the intrinsic moral values of the nurses do not significantly alter the impact of CSR on their commitment to the organisation. These results provide valuable insights for healthcare administrators and policymakers in Pakistan, highlighting the importance of fostering a supportive leadership style and integrating CSR initiatives focused on employees. Such strategies can enhance affective organisational commitment and, consequently, improve the contextual performance of nursing staff in public healthcare settings. The study contributes to the existing literature by clarifying the interplay between CSR, leadership, organisational commitment, and performance within the context of the Pakistani public healthcare sector.